PENGARUH PERSEPSI NILAI, PERSEPSI RISIKO DAN SIKAP TERHADAP NIAT MEMBELI KEMBALI PADA MAKANAN CEPAT SAJI - Devi, Ni Ketut Eugenia Shara; Aksari, Ni Made Asti (E-Jurnal Manajemen, 2020)
As the activities of modern society increases, fast food is an alternative for consumption in today’s instant era. This study aims to describe the influence of perceived value, perceived risk, and attitude on repurchase intention of fast food in quick service restaurants in Indonesia. The study samples consist of 100 Indonesians who have graduated from senior high school and have purchased and consumed fast food. Data were collected through online questionnaires and analyzed using Partial Least Square). Research result found that perceived value positively affect attitude, while perceived risk was found to negatively affect attitude. It indicates that the more value consumers received after purchasing and consuming fast food, their attitude towards fast food are more positive, on the other hand, the higher the risk consumers received, their attitude towards fast food becomes less positive. Attitude was found to positively affect repurchase intention of fast food. Keywords: perceived value, perceived risk, attitude, repurchase intention, fast food.